Linkage of Thomsen disease to the T-cell-receptor beta (TCRB) locus on chromosome 7q35. - Abdalla, J; Casley, W; Cousin, H; Hudson, A; Murphy, E; Cornélis, F; Hashimoto, L; Ebers, G (1992)
The chromosomal localization of the gene for Thomsen disease, an autosomal dominant form of myotonia congenita, is unknown. Electrophysiologic data in Thomsen disease point to defects in muscle-membrane ion-channel function. A mouse model of myotonia congenita appears to result from transposon inactivation of a muscle chloride-channel gene which maps to a region of mouse chromosome 6. The linkage group containing this gene includes several loci which have human homologues on human chromosome 7q31-35 (synteny), and this is a candidate region for the Thomsen disease locus. Linkage analysis of Thomsen disease to the T-cell-receptor beta (TCRB) locus at 7q35 was carried out in four pedigrees (25 affected and 23 unaffected individuals) by using a PCR-based dinucleotide repeat polymorphism in the TCRB gene. Two-point linkage analysis between Thomsen disease and TCRB showed a maximum cumulative lod score of 3.963 at a recombination fraction of .10 (1-lod support interval .048-.275). We conclude that the Thomsen disease locus is linked to the TCRB locus in these families.